The Effect of Enrichment Program on the Achievement of Vocational High School Gifted Students in Mathematics Competitions - Rochayati, Masithoh Yessi; Rochayani, Masithoh Yessi (LPPM STKIP Kusuma Negara, 2024)
The group of gifted students is a group of students who need special services in learning. SMK Negeri 1 Turen, is one of the schools in Malang Regency that has a platform for gifted students, in the form of a mathematics olympiad team. Every year there are beginner students who join the mathematics olympiad team. Therefore, matriculation is needed for them to catch up on the material they are missing. This research was conducted to find out how many enrichment program meetings are needed for beginner students to equalize their abilities with experienced students. The participants in this study were 10 students, consisting of 6 beginner students and 4 experienced students. Based on the Mann-Whitney test, the results of this study indicate that a long-term enrichment program (17 meetings) has a significant effect on students' achievement in mathematics competitions.